The animator's reference book - Pardew, Les (Gale virtual reference library, 2005)
This book is designed to assist animators with the complex challenge of creating accurate human animation. It contains synchronized photos showing a wide range of common human motion, photographed from the front, side, back, and top to provide a complete view of the action and offer a clear, frame-by-frame reference of human movement.